Should students have to borrow?. (May 2016) - Martin, Christopher
Abstract : Since autumn 2012, higher education institutions in England have been able to charge undergraduate students up to £9, 000 a year in tuition fees. Full‐time students are expected to take out loans large enough to cover their tuition fees and living costs for the duration of their studies. They must start repaying these loans if and when their earnings reach £21, 000 a year. In this bold and timely pamphlet, Christopher Martin argues that forcing students to borrow is a serious mistake. He contends that higher education is a welfare good on a par with basic schooling and health care. To flourish in liberal democratic societies, citizens must be personally autonomous, and the educational demands of personal autonomy are too heavy to be met by compulsory schooling alone. To lead autonomous lives, adult citizens need ongoing educational support, support that the liberal democratic state has an obligation to provide. Higher education should therefore be a universal entitlement and free at the point of use. The global debate about who should pay for higher education is by no means settled. As England shifted the financial burden from taxpayers to students, Germany moved in the opposite direction: all German universities have offered free tuition since 2014. Christopher Martin's distinctive contribution to the debate is to lay out a principled argument, based on a plausible assessment of the purpose of higher education, for the view that students should not have to pay for their education. His argument is controversial, to be sure, but it represents a serious and considered attempt to set the question of higher education funding on sure normative foundations.